On the Fijian endemic Nesobasis brachycerca Tillyard, 1924 (Odonata: Coenagrionidae) with first description of the female and updated description of the male - Rashni, Bindiya; Donnelly, Thomas; Sakiti-Waqa, Hilda; Osborne-Naikatini, Tamara; Raituva, Jone; Maiwaqa, Manoa; Maiwaqa, Penaia Valevesi; Marinov, Milen (Zootaxa, 2023)
Nesobasis brachycerca Tillyard, 1924 specimens have been sampled during the course of an ongoing PhD study investigating the utility of Odonata individuals for assessing the conservation importance of the Fijian freshwater resources. Material was analysed and compared to all published records on this taxon. We here provide the first morphological description (by supposition) of the female of N. brachycerca, update the morphological characteristics of the male and present some habitat specifications measured in the field.